2020
DOI: 10.1128/jb.00725-19
|View full text |Cite
|
Sign up to set email alerts
|

Two Routes for Extracellular Electron Transfer in Enterococcus faecalis

Abstract: Enterococcus faecalis cells are known to have ferric reductase activity and the ability to transfer electrons generated in metabolism to the external environment. We have isolated mutants defective in ferric reductase activity and studied their electron transfer properties to electrodes mediated by ferric ions and an osmium complex-modified redox polymer (OsRP). Electron transfer mediated with ferric ions and ferric reductase activity were both found to be dependent on the membrane-associated Ndh3 and EetA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Electroactive organisms can be found in all three domains of life, being ubiquitous in distinct environments, including lakes, soils as well as in deep-sea hydrothermal vents [11] , [12] . Recently, is has been demonstrated that these organisms are also present in the human digestive system [16] , [17] , in the mouse gut microbiome [18] , [19] , [20] and oral plaque [21] , with some of them associated with infectious diseases [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroactive organisms can be found in all three domains of life, being ubiquitous in distinct environments, including lakes, soils as well as in deep-sea hydrothermal vents [11] , [12] . Recently, is has been demonstrated that these organisms are also present in the human digestive system [16] , [17] , in the mouse gut microbiome [18] , [19] , [20] and oral plaque [21] , with some of them associated with infectious diseases [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative mesophilic bacteria are one of the most studied class of electroactive organisms, with most of the knowledge being confined to the model organisms Geobacter sulfurreducens and Shewanella oneidensis MR-1 [2] , [3] , [24] . Nonetheless, Gram-positive bacteria have recently attracted the scientific attention, given their capacity in producing high levels of current in MFC [25] , [26] , and by being associated with infectious diseases in humans [16] , [17] , [22] , [23] . Given the importance of these organisms in BES, research has been dedicated in exploring their use as catalysts in BES and in the understanding of their EET processes [27] , [28] , [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The paper from Hederstedt, Gorton, and Pankratova in this issue of the Journal of Bacteriology (22) uniquely approaches this question by directly comparing ferric iron reduction and EET abilities of E. faecalis mutants. Naturally, ferric iron reduction is an extracellular reaction and thus requires EET.…”
mentioning
confidence: 99%
“…Because one of the E. faecalis NDH-2s (Ndh2) is highly homologous to L. monocytogenes NDH-2, it is likely that this E. faecalis NDH-2 also catalyzes NADH:DMK oxidoreduction and is thus a "conventional" NDH-2. Indeed, Hederstedt et al showed that, using a membrane extract, NADH oxidation activity was associated with NDH-2 (22). Then, the question remains, how do E. faecalis and L. monocytogenes (and other Gram-positive bacteria) utilize multiple NDH-2 enzymes to generate distinctive electron transfer pathways?…”
mentioning
confidence: 99%
See 1 more Smart Citation